2017
DOI: 10.1002/asia.201601676
|View full text |Cite
|
Sign up to set email alerts
|

Cocatalyst‐Free Hybrid Ionic Liquid (IL)‐Based Porous Materials for Efficient Synthesis of Cyclic Carbonates through a Cooperative Activation Pathway

Abstract: Cocatalyst-free ionic liquid (IL)-based porous polymers (P -V -OH R) functionalized with an intermolecular hydroxyl group were prepared by means of radical copolymerization of 1-butyl-3-vinylimidazolium bromide, (4-vinylphenyl)methanol (VBzOH), and divinylbenzene (DVB) under solvothermal conditions. As the ratio of 4-vinylphenylmethanol in the initial mixture increased, the content of the hydroxyl groups in the polymer increased from 3.35 to 5.35 mmol g and the Brunauer-Emmett-Teller (BET) surface area of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 75 publications
(58 reference statements)
2
12
0
Order By: Relevance
“…As expected, 2‐phenyloxirane bearing large steric hindrance gave rise to the target product in low conversion of 66 % (entry 7a), while complete cycloaddition to cyclic carbonate was realized when reaction time was enhanced to 48 h (entry 7b). However, the use of the internal cyclohexene oxide gave 31 % GC yield in 48 h (entry 8a), its lower activity than those of terminal epoxides is consistent with previous reports [10a,20] . It is noteworthy that the reaction of diepoxide with CO 2 generated the target product in a 94 % GC yield after 48 h (entry 9a).…”
Section: Resultssupporting
confidence: 88%
“…As expected, 2‐phenyloxirane bearing large steric hindrance gave rise to the target product in low conversion of 66 % (entry 7a), while complete cycloaddition to cyclic carbonate was realized when reaction time was enhanced to 48 h (entry 7b). However, the use of the internal cyclohexene oxide gave 31 % GC yield in 48 h (entry 8a), its lower activity than those of terminal epoxides is consistent with previous reports [10a,20] . It is noteworthy that the reaction of diepoxide with CO 2 generated the target product in a 94 % GC yield after 48 h (entry 9a).…”
Section: Resultssupporting
confidence: 88%
“…The XRD pattern of all SBA-Zn-TPy + PBr – samples clearly shows a (100) diffraction peak, implying that all samples have an ordered mesostructure similar to SBA-15 (Figure S2). The fading of (110) and (200) diffraction peaks may be due to the occupation of the organic component in the mesopore, which decreases the contrast between the pore and the wall . The TEM image of representative SBA-Zn-TPy + PBr – DMF clearly shows the ordered arrangement of 2-D hexagonal mesopores, further confirming that SBA-Zn-TPy + PBr – has an ordered mesoporous structure.…”
Section: Resultsmentioning
confidence: 65%
“…In 2017, Yang et al developed ionic liquid-based hydroxyl-functionalised porous polymers 51 via the copolymerisation of three monomers (Scheme 27). 165 In polymers 51, the 1-alkyl-3-vinylimidazolium bromide provided the ionic liquid component, 4-vinylbenzyl alcohol provided hydroxyl groups and 1,4-divinylbenzene shaped the porous structure. By comparing different catalysts, it shown that the catalyst with the highest hydroxyl group content and largest BET surface area was the most active.…”
Section: Ionic Polymersmentioning
confidence: 99%